Preparation and Characterization of Itraconazole Microsponges using Eudragit RSPO and Study the Effect of Stirring on the Formation of Microsponges - Monika; Dua, Jagdeep Singh; Prasad, D.N.; Hans, Mansi; Kumari, Satish (Journal of Drug Delivery and Therapeutics, 2019)
The purpose of the present study was to prepare and evaluate Itraconazole loaded microsponges using Eudragit for the controlled release of the drug and study the effect of stirring rate on the formation of microsponges. Microsponges containing Itraconazole were prepared by using quasi-emulsion solvent diffusion method at different stirring rate i.e. 500, 800, 1000, 1200 and 1500rpm.  Particle size of prepared microsponge was observed in the range of 78.43 to 23.18 µm. Scanning electron microscopy revealed the porous, spherical nature of the microsponges. The production yield, entrapment efficiency, and drug content were found to be 80.88%, 84.53% and 82.89%. The formulation with higher drug to polymer ratio 1:10 (i.e. F5) was chosen to investigate the effect of stirring rate on the morphology of microsponges. As the speed was increased, the particle size of microsponges was reduced and uniform spherical microsponges were formed. As drug polymer ratio increased, Production yield, drug content and entrapment efficiency was found to be increased while drug: polymer ratio has reverse effect on particle size, as drug: polymer ratio increase, particle size decreases. The cumulative percentage drug release upto 8hrs for F5 was 89.54% and the mechanism of drug release from the formulations during the dissolution was determined using the zero order, first order, higuchi equation and Peppas equation. All formulations were best fitted to Zero order and peppas plot. The best formulation F5 follows Zero order release.Keywords: Microsponges, Itraconazole, stirring rate, Quasi-emulsion solvent diffusion method